Life cycle considerations of the flue gas desulphurization system at a lignite-fired power plant in Thailand - Sampattagul S. (2014)
Goal, Scope and Background. The Flue Gas Desulphurization (FGD) system has been installed at the biggest lignite-fired power generation plant in Thailand to reduce the large amount of SO2 emission. In order to understand the costs and benefits, both in ecological and economic terms, the lignite-fired plant was studied both before and after the installation of the FGD system. The focus of this study is to consider not only the Life Cycle Assessment (LCA) outcome but also the Life Cycle Costing (LCC) factors. The results can provide valuable information when selecting appropriate technologies to minimize the negative impact that lignite-fired power plants have on the environment. Methods. The Life Cycle Assessment - Numerical Eco-load Total Standardization (LCA-NETS) system was used to evaluate the impact on the environment of both the lignite-fired plant and the FGD system. Life Cycle Costing (LCC) was used to provide a comparison between alternative before and after installation of FGD. LCC, a powerful analytical tool, examines the total cost, in net present value terms, of a FGD system over its entire service lifetime. Results and Discussion. The results of the study are shown in the eco-load values over the entire life cycle of the lignite-fired plant. Comparative models of the power plant, before and after the installation of the FGD system, are evaluated using the LCA-NETS system. The results indicate that the installation of the FGD system can reduce the acidification problem associated with lignite-fired plants by approximately 97%. The LCC estimation shows the major costs of the FGD system: capital investment, operating and maintenance, and miscellaneous costs. The LCC provides the decision-making information when considering the cost of the FGD system in terms of protecting the environment. Conclusion and Outlook. LCA is an important decision-making tool for environmental policies, especially with regard to the selection of pollution control equipment for lignite-fired plants. Green coal technologies and strategies to reduce the negative impact on the environment are essential to produce more environmentally-friendly power plants with a sustainable future.